Wheelmap: the wheelchair accessibility crowdsourcing platform - Mobasheri, Amin; Deister, Jonas; Dieterich, Holger (Open geospatial data, software and standards, 2017)
Crowdsourcing (geo-) information and participatory GIS are among the current hot topics in research and industry. Various projects are implementing participatory sensing concepts within their workflow in order to benefit from the power of volunteers, and improve their product quality and efficiency. Wheelmap is a crowdsourcing platform where volunteers contribute information about wheelchair-accessible places. This article presents information about the technical framework of Wheelmap, and information on how it could be used in projects dealing with accessibility and/or multimodal transportation.